Peran Polisi Kehutanan Dalam Menanggulani Kegiatan Illegal Logging Di Taman Nasional Alas Purwo - Eko Setiawan; Ismi Lufina (Universitas PGRI Palembang, 2024)
Alas Purwo National Park has a variety of potential unique biodiversity and ecosystems, making it important in creating a sustainable relationship with the environment. Threats to the sustainability of conservation areas, one of which comes from illegal logging activities that have been categorized as extraordinary crimes. This article aims to answer problems related to illegal logging, the role of the Forestry Police and its obstacles in tackling illegal logging activities in Alas Purwo National Park. This research uses a qualitative approach in the form of a case study. Data collection methods by observation, in-depth interviews, documentation. Data analysis using interactive models, including the stages of data collection, data reduction, data presentation and conclusions.Various efforts have been made by the Forestry Police to tackle illegal logging activities, but there are still obstacles on the ground. Therefore, this article is expected to be a contribution of thought for policy makers, both at the regional and central levels.